DEKONSTRUKSI KOMUNIKASI POLITIK PADA PELAYANAN E-COMMERCE (PERSPEKTIF ANALISIS WACANA KRITIS FAIRCLOUGH) - Susanto, Adi (MEDIASI, 2020)
Deconstruction of Political Communication on E-Commerce Services (The Perspective of Fairclough’s Critical Discourse Analysis). This research is motivated by crime issues that have developed into various social crimes, such as cyber crime, psychological crime, economic crime, and political crime. In the digital era, the crime of political communication is new because this form of crime is sublimated in e-commerce which tends to appeal to all E-Commerces. Critical discourse analysis offers a critical perspective in addressing the latest phenomena facing humans in the E-Commerce. Specifically, the phenomenon of technology whose development is increasingly fast and uncontrollable. The purpose of this study is to reveal various forms of political communication crime through critical discourse analysis. The method used in this research is the library method. The results showed that the crime of political communication in the E-Commerce occurred through the medium of the Digital Market as a medium of political communication.